2022
DOI: 10.1177/00943061221103313
|View full text |Cite
|
Sign up to set email alerts
|

The Sociology of Disability-Based Economic Inequality

Abstract: why-employment-isnt-a-good-indicator-ofeconomic-well-being/ 250 Featured Essay Contemporary Sociology 51, 4 Featured Essay 251 Contemporary Sociology 51, 4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 143 publications
(148 reference statements)
0
5
0
Order By: Relevance
“…In the 33 years since the passage of the ADA and the IDEA, sociological research has made great progress in illuminating the sources and consequences of various social inequalities. However, disability has remained largely absent from mainstream sociological work on stratification (Barnartt 2013; Maroto and Pettinicchio 2015; Pettinicchio et al 2022). A recent review of articles ever published in the discipline’s flagship journals, American Sociological Review and American Journal of Sociology , found only nine articles that listed disability as a keyword; the majority of these were published over 20 years ago (Gerschick and Stevens 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the 33 years since the passage of the ADA and the IDEA, sociological research has made great progress in illuminating the sources and consequences of various social inequalities. However, disability has remained largely absent from mainstream sociological work on stratification (Barnartt 2013; Maroto and Pettinicchio 2015; Pettinicchio et al 2022). A recent review of articles ever published in the discipline’s flagship journals, American Sociological Review and American Journal of Sociology , found only nine articles that listed disability as a keyword; the majority of these were published over 20 years ago (Gerschick and Stevens 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Maroto and Pettinicchio (2015:2) observe that disability “remains a disproportionately small part of the mainstream literature on structural inequality. Given the size of the population with disabilities in the United States and the hardships they face, it is particularly surprising that disability is often excluded from general sociological studies of stratification and inequality” (see also Barnartt 2017; Pettinicchio, Maroto, and Brooks 2022). Nevertheless, there are robust literatures on disability in disability studies, the sociology of disability, and medical sociology.…”
Section: Disability and Inequalitymentioning
confidence: 99%
“…It seems that this applies to Iran; in the current status of the Iranian economy, there are few job opportunities for the labor force, and extended families will have less income and more expenses.Therefore, it is recommended to use policies to increase the welfare of extended households to reduce this increased inequality in disability. Also, it seems that these policies can be effective for families with disabled members in order to better cope with the burden of disability ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Extending stress process models, minority stress frameworks emphasize how chronic stressors experienced through status and group membership lead to disproportionate negative mental health outcomes (Meyer, 2003;Meyer & Frost, 2013;Schwartz & Meyer, 2010). Disability, particularly as it intersects with health, is a key axis of inequality (Mauldin, 2023;Maroto & Pettinicchio, 2023;Pettinicchio et al, 2022), affecting everything from jobs, to government supports, to adequate health care.…”
Section: The Chronic Stress Of Precarity Among People With Disabilitiesmentioning
confidence: 99%